Impact of Half Squat Jumps and Resistance Band Exercises on High School Students' Basketball Shooting Accuracy - A. Musdalifah; Muhammad Kamal; Muh. Said Hasan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Shooting accuracy is a crucial element in basketball, but student athletes often face consistency issues due to a lack of explosive leg muscle power. This study aims to examine the impact of half squat jump and resistance band training on basketball shooting accuracy in students at High School 16 Makassar. Using experimental research design, this study involved 20 basketball players selected through total sampling. The main instrument used was a free throw test, with data analyzed through descriptive statistics, normality tests, homogeneity tests, and t-tests. The results showed: (1) There is a significant effect of half squat jump training on shooting accuracy (t_count = 11.196 > t_table = 1.833; p < 0.05) which contributes to increasing explosive leg muscle power. (2) There is a significant effect of resistance band training on shooting accuracy (t_count = 7.562 > t_table = 1.833; p < 0.05) which strengthens the kinetic chain for shooting stability. (3) Independent sample t-test showed a significant difference in effectiveness between the two methods (t_count = 4.352 > t_table = 2.101; p < 0.05), where both modalities provide different physiological adaptations. Collectively, both methods are effective strategic solutions, but resistance band training showed a tendency for higher results in improving accuracy compared to half squat jumps. This study provides practical contributions for coaches in developing varied physical programs to improve the technical performance of high school level players.